Belgian Rule and its Afterlives: Colonialism, Developmentalism, and Mobutism in the Tanganyika District, Southeastern DR-Congo, 1885–1985. (10th November 2017) - Loffman, Reuben
Abstract: The arrival of Belgian rule in the late nineteenth century initiated significant changes in the labor history of Tanganyika, a province in the southeastern Democratic Republic of the Congo (DRC), as well the discursive regimes used to legitimize these transformations. After the colonial conquests, unfree labor was justified by paternalistic rather than mythical discourses. Although unfree labor was less common in the postcolonial period, the state forced farmers to sell crops at low prices and build roads for no remuneration. In the Cold War context, the language and practice of developmentalism mediated the coercive practices of the independent Congolese state (known as Zaïre, 1971–1997). The floundering Zaïrian government expanded its presence in Tanganyika due to its partnership with USAID. USAID's rhetoric and practice was influenced by a "bottom up" approach to agricultural production, but the cuts to its funding in the 1980s meant it struggled to soften Mobutu's coercive administration.